Production of bio resin from palm oil - Nur Syazana, Md Nazri (2014)
Nowadays, the demand for fossil fuels is quite high. But, the extensive use of fossil fuels is causing the gradual decrease of fossil fuels. Therefore, a way to get rid of widespread of using fossil fuels is by developing a new renewable source that can benefit our environment. Resin is one of the important polymeric in the chemical industry. Resins such as alkyd resins are widely used in coatings and paint industry. There are many researches about producing a resin from renewable sources such as vegetable oils. The naturally used vegetable oils in producing resin are soyabean, rapeseed, coconut, castor or linseed oils. Other than that, there are many potential vegetable oils such as karawila, nahar, rubber or safflower oil. Scientist and engineers are dedicated to find another alternative to replace using fossil fuels as the main components in resin making. This study was inspired to do a research by using palm oil as the main components in making renewable resin or bio resin. In this study, waste cooking oil was used as the main component in making bio resin. The synthesis of resin begins with alcoholysis of waste cooking oil with glycerol followed by esterification process. Then, the monoglyceride was reacted with anhydride to obtain bio resin. The resulting product which is bio resin was characterized for physiochemical properties, thermogravimetric analysis (TGA), the infrared spectrum using Fourier Transform Infrared Spectroscopy (FTIR), melting point using Differential Scanning Calorimeter (DSC). The result was compared with previous literature about producing resin from renewable material such as karawila seed oil. The expected resin is feasible in replacing synthetic resin. Thus, improvements and more research need to be made as to market the resin.